Effect of Meniran Extract (Phyllanthus niruri Linn.) on Histological Structure Damage in Mice (Mus musculus Linn.) Induced by Paracetamol - Denalia Aurika; Ratih Dewi Yudhani; Muthmainah Muthmainah (Nexus Biomedika, 2016)
Introduction: Drug Induced Liver Injury (DILI) is a liver injury caused by drug toxicity. About 41 out of 100.000 people suffer liver damage due to DILI. Most of this injury caused by excessive use of paracetamol. Meniran (Phyllanthus niruri Linn.) contains antioxidants that can protect liver from damage. The aim of this research was to investigate the hepatoprotective effect of meniran extract on histological damage in liver cells induced by paracetamol. Methods: This was laboratory experimental research with post test only controlled group design. This research was conducted in Histology Laboratory FK UNS. Samples were 30 mice obtained by purposive sampling which characteristics were Swiss webster type, male, 2-3 months old, 20 gr of each weight. Samples divided randomly into 5 groups, each group has six mice. The normal group (KN) was given distilled water only. The negative control group (KK (-)) was given paracetamol toxic dose only. The positive control group (KK (+)) was given Curcuma and paracetamol toxic dose. A gradual dose (2.8 mg and 5.6 mg) of meniran extract was given daily to the first treatment group (KP 1) and second treatment group (KP 2) for 14 days respectively and added with paracetamol toxic dose (5 mg) on day 8th to 14th orally. On day 15th, mice were sacrificed and liver were taken for preparation with HE staining. Liver cells damage was identified by counting nucleus with pyknosis, karryorhexis, and karyolysis from 100 liver cells. Data was analyzed using One-Way ANOVA and Post Hoc Multiple Comparisons-LSD (? = 0.05). Results: One-Way ANOVA showed that there was a significant difference between 5 groups (p < 0.05). Post Hoc Multiple Comparisons-LSD showed that there were significant differences (p < 0.05) between KN-KK (-), KN-KK (+), KN-KP 1, KN-KP 2, KK (-)-KK (+). KK (-)-KP 1, KK (-)-KP 2, KK (+)-KP 1, KP 1-KP 2, but there was not significant difference between KK (+)-KP 2 (p > 0.05). Conclusions: Meniran extract has hepatoprotective effect on histological structure damage of mices liver cells induced by paracetamol in a dose dependent manner. Keywords: Phyllanthus niruri, paracetamol, liver cells histologic damage